2017
DOI: 10.1017/s1751731116002196
|View full text |Cite
|
Sign up to set email alerts
|

Production objectives, trait and breed preferences of farmers keeping N’Dama, Fulani Zebu and crossbred cattle and implications for breeding programs

Abstract: Many local livestock breeds in developing countries are being replaced by exotic breeds, leading to a loss of genetic resources. In southern Mali, for the past two decades, a trend towards increasing crossbreeding between the trypanotolerant N'Dama cattle and the trypano-susceptible Fulani Zebu cattle has been taking place. A survey with 160 farmers owning a cattle herd was carried out in southern Mali to investigate their production objectives, as well as trait and breed preferences and correlated socio-econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 24 publications
3
32
0
Order By: Relevance
“…However, whenever a zebu bull is maintained in a Lagune cattle herd, the farmer tends to mate it with all cows present in the herd. These results are in accordance with findings of Sokouri et al (2009) in the northern region of Côte d'Ivoire and of Traoré , Markemann, Reiber, & Piepho (2017) in South Mali.…”
Section: Discussionsupporting
confidence: 93%
“…However, whenever a zebu bull is maintained in a Lagune cattle herd, the farmer tends to mate it with all cows present in the herd. These results are in accordance with findings of Sokouri et al (2009) in the northern region of Côte d'Ivoire and of Traoré , Markemann, Reiber, & Piepho (2017) in South Mali.…”
Section: Discussionsupporting
confidence: 93%
“…Trait preferences for cattle found in this study reflect the multiple needs of smallholder farmers in Zimbabwe, and are comparable with the findings of similar studies conducted in Southern Mali (Traoré et al, 2017) and Kenya (Bebe et al, 2003). Rowlands et al (2003) reported that the five traits farmers in Zimbabwe perceived by to be most important were size, adaptability, growth, temperament and fertility.…”
Section: Preference For Breeds and Traitssupporting
confidence: 87%
“…In the context of climate change and variability, the adaptive traits of preferred Sanga cattle breeds justify the need for conservation of these unique breeds as insurance against unforeseen future changes (Traoré et al, 2017). Therefore, the use of principally Sanga, Brahman and Brahman based composite breeds may be considered the most suitable breeding strategy for smallholders in Southern Africa.…”
Section: Preference For Breeds and Traitsmentioning
confidence: 99%
See 2 more Smart Citations